Levantamento de Meloidogyne exigua na cultura da seringueira em São José do Rio Claro, MT, Brasil - Bernardo, Eduardo Roberto de Almeida [UNESP]; Santos, Jaime Maia dos [UNESP]; Silva, Ricardo Adaime da [UNESP]; Cassetari Neto, Daniel; Santos, Suzana Souza dos; Delmadi, Leila; Rocha, Vander de Freitas (Universidade Federal de Santa Maria (UFSM), 2003)
Este trabalho foi realizado com o objetivo de efetuar um levantamento da ocorrência de Meloidogyne exigua em seringueira em São José do Rio Claro, MT. Foram amostradas 191 propriedades agrícolas, totalizando cerca de 18.000ha. Os nematóides foram identificados no Laboratório de Nematologia do Departamento de Fitossanidade da FCAV/UNESP, em Jaboticabal, SP. Foram encontrados níveis populacionais de M. exigua entre 0 e 61.824 juvenis/5g de raízes.

This study was carried out aiming to evaluate the Meloidogyne exigua occurrence on rubber tree in São José do Rio Claro, MT, Brazil. One hundred ninety one agriculture holdings were sampled, totalizing around 18000ha. The nematodes were identified in the Nematology Laboratory, Department of Fitossanidade, FCAV/UNESP, Jaboticabal, SP. Population levels of M. exigua between 0 and 61824 juveniles/5g of roots were observed.
Meloidogyne exigua survey on rubber tree in São José do Rio Claro, MT, Brazil
Keywords: root-knot nematode; Meloidogyne exigua; Hevea brasiliensis; Botryodiplodia theobromae; Nematóide das galhas; Meloidogyne exigua; Hevea brasiliensis; Botryodiplodia theobromae